2019
DOI: 10.1530/erc-18-0226
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine differentiation of prostate cancer leads to PSMA suppression

Abstract: Prostate-specific membrane antigen (PSMA) is overexpressed in most prostate adenocarcinoma (AdPC) cells and acts as a target for molecular imaging. However, some case reports indicate that PSMA-targeted imaging could be ineffectual for delineation of neuroendocrine (NE) prostate cancer (NEPC) lesions due to the suppression of the PSMA gene (FOLH1). These same reports suggest that targeting somatostatin receptor type 2 (SSTR2) could be an alternative diagnostic target for NEPC patients. This study evaluates the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(94 citation statements)
references
References 44 publications
3
83
0
Order By: Relevance
“…Some case reports described that PSMA-targeted PET/CT may be not able to detect neuroendocrine prostate carcinoma [38][39][40]. Supporting these observations, Bakht et al (2018) demonstrated in vitro on patient-derived xenograft (PDX) an inverse correlation between PSMA gene (FOLH1) and neuroendocrine biomarker gene expression [41]. Particularly, suppression of the PSMA gene was observed in 65% of cases which overexpressed the NSE gene (ENO2).…”
Section: Discussionmentioning
confidence: 98%
“…Some case reports described that PSMA-targeted PET/CT may be not able to detect neuroendocrine prostate carcinoma [38][39][40]. Supporting these observations, Bakht et al (2018) demonstrated in vitro on patient-derived xenograft (PDX) an inverse correlation between PSMA gene (FOLH1) and neuroendocrine biomarker gene expression [41]. Particularly, suppression of the PSMA gene was observed in 65% of cases which overexpressed the NSE gene (ENO2).…”
Section: Discussionmentioning
confidence: 98%
“…As mentioned above, higher SUV mean is generally associated with higher dose delivery through PSMA targeted therapy [25]. If more aggressive prostate cancer cell phenotypes evolve, the PSMA expression might decrease [26]. Because of that, FDG PET is sometimes performed in addition to PSMA PET, which helps to detect dedifferentiated metastases [12].…”
Section: Discussionmentioning
confidence: 99%
“…Prostate-specific membrane antigen (PSMA) was found as the most significantly decreased protein in LNCaP-Trop2-OV tumors ( Fig. 5 A and B), and PSMA is known to be suppressed in NEPC (23). We further investigated the effect of Trop2 on PARP1 and AR levels.…”
Section: Trop2 Drives Neuroendocrine Phenotype and High Levels Of Parp1mentioning
confidence: 97%